PWE-101 Imaging The Small Bowel In Ulcerative Colitis-relevant Or Still ''unclassified"?. (9th June 2014) - Singh, S; Aggarwal, D; Limdi, JK
Abstract : Introduction: It is widely accepted that Ulcerative Colitis (UC) is a mucosal inflammatory disease confined to the colon. Bolder disease definitions coupled with novel and evolving imaging paradigms have led to more sophisticated small bowel imaging in recent years. Despite this, studies on the relevance and yield of small bowel pathology in UC patients are limited. Methods: We conducted a retrospective review of consecutive UC patients seen at our institution between May-October 2013. Clinical data for demographics, disease characteristics, small bowel investigation, endoscopy, treatment and clinical outcomes were obtained from electronic patient records. Results: We analysed 321 patients with biopsy confirmed UC [61% male, mean age 53 yrs, range 18–91 yrs]. Mean age of diagnosis was 43 yrs and mean disease duration was 10 yrs. Montreal classification was E1 (14%), E2 (49%) and E3 (37%) respectively. Forty-seven patients had small bowel investigations: MR enterography in 81%, CT enterography in 15% and barium follow-through in 4%. Disease severity at the time of small bowel imaging was mild to moderate in 68% and 32% had severe disease. Thirty-two percent of patients were on thiopurines, 19% on bimodal immunosuppression (infliximab + thiopurine) and 49% were on aminosalicylates. Seven patients had undergone colectomy. Small bowel imaging was reported normal in 46/47 and one patient had distal and terminal ileal disease. Indications for small bowel imaging are shown in Table 1 . Subsequent to small bowel imaging, 40% (19/47) had no change in therapy, 43% were escalated to immunosuppressive therapy and 11% underwent surgery for UC. In 3 patients, the diagnosis was changed from UC to Crohn's disease (2 with perianal Crohn's; 1 with small bowel Crohn's based on MRE) all subsequently treated with Anti-TNF therapy. Conclusion: The yield of small bowel pathology in our cohort was low, supporting current European Crohn's and Colitis Organisation (ECCO) recommendations. 1 Small bowel imaging in UC meanwhile should be considered in the well-selected patient and driven by the clinical question or diagnostic uncertainty. Reference: Dignass A, Eliakim R, Magro F et al . Second European evidence-based consensus on the diagnosis and management of ulcerative colitis part 1: definitions and diagnosis. J Crohns Colitis . 2012 Dec;6(10):965–90 Disclosure of Interest: None Declared.